A STUDY ON ENTREPRENEURIAL CULTURE IN KAYALPATNAM (International Journal of Food and Nutritional Sciences, 2022)
The rapid growth in entrepreneurial development in Kayalpatnam, together with the strength of culture adopted by entrepreneurs, provides us with a somewhat unique context to investigate: How does culture shape the sourcing of entrepreneurial opportunities? Why some people at Kayalpatnam are more entrepreneurial than others? What motivates these people towards business entry and self-employment? The study area of author is already an entrepreneurial culture, so the problem is why it is so? Why the people residing at Kayalpatnam don’t are not preferring salaried job? In this paper we use a more direct and more complete indicator for entrepreneurial culture.